Transient increase of Ca2+ uptake as a signal for mating pheromone-induced differentiation in the heterobasidiomycetous yeast Rhodosporidium toruloides. - Miyakawa, T (1985)
The role of Ca2+ for the signaling of rhodotorucine A, a mating pheromone of Rhodosporidium toruloides, was investigated. The efficiency with which the target cells responded to the mating pheromone was dependent on the Ca2+ concentration in the medium. The pheromone induced a very rapid and transient increase of Ca2+ uptake in the recipient cell. We concluded that the transient increase in the intracellular Ca2+ concentration could play an essential role in the control of differentiation by the pheromone.